Fire early warning operacional services for ARISTOTLE-eENHSP project - Seco, Daniela Sofia Almeida (2024)
The present report, carried out in “Instituto Português do Mar e da Atmosfera“ (IPMA), aims to describe the procedures used to the monitoring of fire weather danger and to supply fire early warning advice within the scope of the ARISTOTLEeENHSP project. This is an operational program that embraces a multi-hazard scientific assessment for a broader set of risks also including earthquakes, tsunamis, volcanos, severe weather and floods. The information regarding danger assessment is clustered in one single report that is then sent to the Emergency Response Coordination Centre (ERCC), incorporating the most vulnerable regions for each type of risk. The final document is organised by a set of events concerning the risk and the level of danger that, in turn, is selected according to a matrix that takes into account the probability of how the risk affects the population (High, Medium and Low) and the estimated resources needed (Sub-National, National and International). During the first months of this internship, the main focus was on the theoretical understanding of fire activity, danger indexes, platforms and methodologies used and, in the assessment’s elaboration for some of the events that were then compared with the ones performed by the IPMA fire team. At a later stage, I had the opportunity to be part of the team in an operational component and, therefore, the second part of this report is more directed at the analysis of indexes that propelled the fire weather danger during the 2023 summer. To monitor fire danger, the initial assessment is executed by two online platforms, namely, the European Forest Fire Information System (EFFIS) and the Global Wildfire Information System (GWIS), that provide differentiated information, about fire danger indexes (FWI, ISI, FFMC, DC, DMC and BUI) of the Canadian Forest Fire Danger Rating System (CFFDRS), vegetation and fuels type, active fires, past occurrences, anomalous values and ranking. These data are then crossed with the weather forecast supplied by the European Centre for Medium-Range Weather Forecasts (ECMWF). In general, it was verified that the service needs were high during June, July and August over the Mediterranean region related to severe meteorological conditions of dry and hot weather (heatwave episodes), combined with flammable vegetation, low moisture content on fuels and in the proximity to urban and touristic areas. July was the month with the highest number of events (14 of routine and 3 of emergency). Relatively to my development in the internship, the main difficulties felt were in the choice of the risk matrix level alert, however, the operational support provided to the IPMA’s fire team during the peak of the fire season allowed the accomplishment of the internship’s purposes.